GENETIC DIVERGENCE ANALYSIS OF SESAME GENOTYPES (Sesamum indicum L.) - DASARI RAJITHA; T. SRIKANTH; D. PADMAJA; T. KIRAN BABU (The Bioscan, 2020)
Divergence studies through Mahalonobis D 2 statistic on 50 sesame genotypes indicated the presence of substantial diversity by forming large number of clusters with wide range of inter-cluster distances. The 50 genotypes were grouped into 14 clusters based on the D 2 values. Among the fourteen clusters, cluster II was the largest comprising of fourteen genotypes followed by cluster V with ten genotypes, cluster III with nine genotypes, cluster I with seven genotypes. The genotypes JCS 3980, Swetha thil, GT 10, JCS 4039 and JCS 4053 from these clusters having high mean values and may be directly used for adaptation or may be used as parents in future hybridization programme. The highest inter cluster distance was found between clusters VII and XII, while lowest was between IV and VII. The maximum intra cluster distance was recorded for cluster V followed by cluster II. Among all the traits studied, maximum contribution towards genetic divergence was shown by days to 50 per cent flowering followed by days to maturity, oil content, seed yield per plant and number of seeds per capsule. Greater genetic divergence was found between clusters VII and XII indicating superior and novel recombinants and explore the fullest range of variability for the characters and to realize good recombinant can be realized by mating between the lines of these clusters in a definite fashion.